Paysage. Langage. Voyage - Agnès Juvanon du Vachat (Projets de Paysage)
This article analyzes the descriptions of Andalusia gardens and landscape in travel books of French travellers in the nineteenth century. It presents the obstacles in terms of language and lexicon faced by the travellers and their solutions developed to surmount them.